Denitrification Capacity of the Widely Distributed Soil Series of the Turkish Republic of Northern Cyprus - COSKAN, ALI; GOK, MUSTAFA; DOGAN, KEMAL (Asian Journal of Chemistry, 2010)
A laboratory experiment was carried out to determine the denitrification capacity of the Doganci, Geçitkale, Akdeniz, Balikesir, Pamuklu, Zümrütköy and Türkmenköy that are widely distributed soil series of Turkish Republic of Northern Cyprus. Soils are placed in anaerobic jars (20 % initial O2, 80 % He) with addition of 300 mg kg-1 NO3--N. Produced gases (CO2, N2 and N2O) along with O2 consumption were determined by gas chromatography. Moreover, ammonium and nitrate concentration of the soils were measured at regular intervals. The measured O2 consumption and CO2 production values as parameters of biological activities revealed considerable differences among the soil series studied. The more rapid O2 consumption and the higher CO2 production were determined in Balikesir, Zümrütköy and Türkmenköy soil series. Furthermore, O2 level in the anaerobic jar was immediately dropped in early measurement intervals and was about 0 % at the end of the last measurement, particularly above mentioned soil series. The Zümrütköy soil series has higher CO2 production in all measurement periods than the others and reached 975 μg CO2 g dry soil-1 at the end of experiment where others vary from 257 to 745. The measurements of N2O and N2 gases revealed that the most of the denitrification product consists of N2. Additionally, the highest N2O and N2 productions were determined in the Balikesir series with 251 μg N2O-N g dry soil-1 and 498 μg N2-N g dry soil-1. When all series compared, there were significant differences for the production of N2 and N2O production. Nitrate and ammonium analyses measured in relation to time, ammonium content was similar in all series, however, nitrate content significantly decreased according to the measurement period.